Groups of Research: An Approximation from an Ethical Point of View - María Bertha Fortoul Olliver (Universidad Autónoma de Madrid, 2016)
Academic research is a socio-historical multi-faceted practice in which those who do it leave their footprint, starting from the assumption of the presence of ethical aspects of science.  The article is centered on the relationship between researchers, the researcher and his graduate students working in groups of research focusing on the respect granted to the other participants.  Through documental and empirical information it is recognized that in a collective production of knowledge, it's possible to take care of or crush some the members at some point.  Analytical categories like balance between cohesion and precision, the conformation of professional ethos, tension between equals and submitting and formation for the jobs that let us describe group dynamics.  The article ends rescuing research as a human activity, in the relation with others and as result in need of the inclusion of ethical criteria.